Pepper Production in Miami-Dade County, Florida - Qingren Wang; Shouan Zhang; Yuncong Li; Dakshina R. Seal; Waldemar Klassen; Teresa Olczyk (EDIS)
Pepper is an important vegetable crop in Miami-Dade County. Unlike other vegetable crops, peppers are relatively more adaptable to the environment, especially the heat, and are relatively easier to grow. But to be successful, careful attention must be paid to maintain healthy plants and high productivity with efficient management of soil and water for the particular needs of each variety or cultivar. This revised 7-page fact sheet provides general information and guidelines for pepper growers in Miami-Dade County, including major pepper varieties, and their horticultural traits, and fundamental soil and water management requirements. Written by Qingren Wang, Shouan Zhang, Yuncong Li, Dakshina Seal, Waldemar Klassen, and Teresa Olczyk, and published by the UF Department of Horticultural Sciences, February 2015.